Pengembangan Media Pembelajaran Articulate Storyline Pada Materi Dasar-Dasar Perhotelan di SMK Negeri 1 Singaraja - Putri, Ketut Windi Tarisa; Sukerti, Ni Wayan; Ariani, Risa Panti (Peneliti.net, 2026)
Abstract: This study aimed to describe the stages of developing learning media based on Articulate Storyline on the material of Hospitality Basics, for Phase E students at SMK Negeri 1 Singaraja. The method used is (Research and Development) with the ADDIE model, which consists of five stages, namely Analyze, Design, Development, Implementation, and Evaluation. (a) Analyze, needs identification is carried out through the distribution of questionnaires and interviews with teachers and students. (b) Design includes designing the media structure, interface display, material preparation, and designing interactive quizzes. (c) Development, learning media is developed using the Articulate Storyline 3 application and validated by experts. The results of the study show that in the (d) Implementation stage which was carried out through field trials on 40 Phase E Hospitality C students, the percentage results were 84.95% which is in the very good category. Furthermore, the students' responses obtained an average score of 58.95 with a very good category, while the teachers' responses obtained an average score of 41.5 with a very good category. (e) Evaluation was carried out to assess the overall suitability of the media based on input from experts, teachers, and students. Keywords: Media Development, Articulate Storyline, Dasar-Dasar Perhotelan , ADDIE.